2002
DOI: 10.1046/j.1524-475x.2002.t01-1-10602.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of anaerobic cocci in impaired human wound healing

Abstract: Although more than 80% of infected and 70% of noninfected leg ulcers have been shown to harbor anaerobic organisms, their role in mediating impaired wound healing in the skin is frequently overlooked. There is now increasing evidence that the gram-positive anaerobic cocci play a role (both directly and indirectly) in mediating impaired wound healing in vivo. This article discusses the mechanisms by which these microorganisms may interfere with the inflammation, repair, and remodeling phases of the wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 69 publications
(65 reference statements)
2
27
0
1
Order By: Relevance
“…They also release short-chain fatty acids that have been shown to inhibit proliferation of fibroblasts, keratinocytes, and endothelial cells (Heerdt et al, 1997). Short-chain fatty acids may also be the causative agent of the malodor associated with anaerobic organisms, and may also contribute to hyperlipidemia associated with very large wounds, which slows wound healing in diabetic and nondiabetic patients (Wall et al, 2002).…”
Section: Pressure Ulcersmentioning
confidence: 99%
“…They also release short-chain fatty acids that have been shown to inhibit proliferation of fibroblasts, keratinocytes, and endothelial cells (Heerdt et al, 1997). Short-chain fatty acids may also be the causative agent of the malodor associated with anaerobic organisms, and may also contribute to hyperlipidemia associated with very large wounds, which slows wound healing in diabetic and nondiabetic patients (Wall et al, 2002).…”
Section: Pressure Ulcersmentioning
confidence: 99%
“…These wounds harbour a diverse microflora, which contributes both directly and indirectly to their non-healing phenotype (Stephens et al, 2003;Wall et al, 2002). Much attention has recently been focused on the ability of the bacteria within chronic wounds to form and exist within a biofilm (James et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that when optimal specimen collection, transport, and culture techniques are used, multiple organisms are usually recovered from DFIs (6,14,23,29,30,45,55). Furthermore, some studies suggest that the interactions of organisms within these polymicrobial mixtures lead to the production of virulence factors, such as hemolysins, proteases, and collagenases, as well as short-chain fatty acids, that cause inflammation, impede wound healing, and contribute to the chronicity of the infection (5,52,53,56). In such mixtures, biofilms that impede the penetration of antimicrobial agents into the infected site may also form (25).…”
mentioning
confidence: 99%